Propostas de simplificação de definições de termos para a divulgação científica: um estudo contrastivo por meio de corpora - Santos, Candice Guarato (2023)
The lexicon offers language users different possibilities of adapting language so that everyone, in different contexts, can communicate, understand, and be understood. This condition is also applicable to the elaboration of definitions of terms, typical of the specialty areas. Based on this question, the objective of this research is to propose paradigms of definitions to help specialists, journalists and lay people who intend to simplify the definitions of terms in their science dissemination texts. The theoretical foundation of this study is based on the Communicative Theory of Terminology, by Cabré (1998), on the Sociocognitive Terminology Theory, by Temmerman (2004), on Accessible Scientific Writing, by Finatto (2022), on Text Simplification, by Paraguassu (2018), and on the structures of definitions of terms in science communication, by Pilkington (2019). Corpus Linguistics, with Berber Sardinha (2006), guided the methodology of this research and the lexical analysis software used was WordSmith Tools (SCOTT, 2020). Four kinds of corpora were compiled: a specialized corpus, with texts written by specialists to other specialists; a specialized corpus of science dissemination, made up of texts written by specialists for lay people; a journalistic corpus of scientific dissemination, consisting of texts written by journalists for laypeople; a lay corpus of science dissemination, composed of texts and subtitles of videos produced by lay people for other lay people. Four subareas of Angiology and Vascular Surgery were chosen for the application of this study, namely “Abdominal Aortic Aneurysm”, “Aortic Dissection”, “Diabetic Foot” and “Thrombosis”. Each of these corpora supported the elaboration of four levels of definitions for the same terms, which were inserted in the VoTec platform (FROMM; LIMA, 2022). The definitions, based on corpora, were processed through NILC-Metrix, under the new Dale Chall Formula and Flesch Index metrics, to calculate the readability index, and through Simpligo to assess sentence complexity. After elaborating the definitions and analyses, two paradigms were proposed for the textual simplification, by substitution of the definitions. The horizontal definitional paradigm is based on the prototypical, procedural, and figurative models of definition. The vertical definitional paradigm guides the replacement of descriptors with specialized semantic feature by other more recurrent descriptors in the general lexicon of the language. The metrics analysis also pointed out that the term can be replaced by its own definition, making the text simpler to understand, and therefore more accessible. The proposals of the horizontal and vertical definitional paradigms can be applied to other areas of knowledge. This study presents contributions to Linguistics, especially Terminography, Accessible scientific writing, Text Simplification, and popularization of specialized languages in addition of providing resources for the scientific dissemination process.